Recent trends in algebraic development techniques : 22nd International Workshop, WADT 2014, Sinaia, Romania, September 4-7, 2014 : revised selected papers /: 22nd International Workshop, WADT 2014, Sinaia, Romania, September 4-7, 2014 : revised selected papers. (2015) - Unknown
No abstract available